L’Arctique et l’internationalisme inuit - Jull, Peter (Études internationales, 1989)
The driving force behind Inuit interest in international affairs has been the determination to solve the problems of under-development, environmental damage, social injustice, inadequate legal recognition and limited or non-existent self-government. To assist in the solution of these problems, the Inuit Circumpolar Conference (ICC) was founded in 1977. The Conference, which is presently headed by a Canadian Inuit (Mary Simon), holds a general assembly every three years and serves as the vehicle for overall Inuit identity and interests in the world. This identity has been developed in spite of international boundaries and East-West conflicts. Thus, the next general assembly, to be held in Sisimiut (Green-land) in 1989, will be the first where Soviet Inuit will join their kin from Alaska, Canada and Greenland. They will continue to address such fundamental issues as: the development of an overall Arctic policy ; the protection of the environment; sustainable development; international aboriginal rights; and the ongoing militarization of the Arctic, which is a cause of great concern to all Inuit.